Social Benefit–Cost Ratio of the Interventions in the Coconut BasedHomesteads of Central Kerala (Indian Journal of Extension Education, 2010)
Analysis of Social benefit – cost ratio of the interventions in the coconut based homesteads of Central Kerala was carried out. It showed that all the six dimensions of Social Cost Index Value (SCIV) were found as the lowest in High Elevation- Medium Rainfall (HEMR) situation (Kizhakkanchery). Among all the dimensions, exploitation by middlemen was rated as the maximum Social Cost Index Value (SCIV) in almost all the situations and therefore this dimension required the attention of policy makers to ensure suitable price for the farm produce. Among the six dimensions in the Social Benefit Index Value (SBIV), family labour utilisation and self confidence were the dimensions which contributed maximum to Social Benefit Index Value. It indicated that the interventions made in the homesteads better utilized family labour and enhanced the self confidence of the participating farmers. Social Benefit Cost Ratio was computed as the highest with 2.04 at High Elevation- Medium Rainfall (HEMR) situation (Kizhakkenchery) and the lowest with 1.07 at Medium elevation- Low Rainfall (MELR) situation (Eruthenpathy) after 18 months of interventions. It was concluded that the interventions on restructuring of coconut based homesteads were economically viable and socially desirable.